EFFECT OF SEASONAL VARATION ON MULTIVOLTINE COCOON YIELD AND GRANAGE PERFORMANCE IN POPULAR MULTIVOLTINE HYBRIDS OF BOMBYX MORI L. UNDER TROPICAL CONDITION IN WEST BENGAL - SAHA, L.M.; CHANDA, S.; KAR, N.B.; MITRA, P.; MANDAL, K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2011)
The present study is an attempt to evaluate the role of Seasonal variation on silkworm seed cocoon and commercial seed production. Rearing of Nistari and M2(W) (Bombyx mori L.) P1 disease free layings (Basic seeds) of two multivoltine silkworm breeds were conducted at seed farmers' level in 2 villages, in Uttar Dinajpur district, West Bengal, during Summer (May), Rainy (June-July) and Spring (Feb-March) in 03 consecutive years under agro-climatic conditions. Similarly grainage was conducted with the seed cocoons in the same seasons in 03 consecutive years for production of multivoltine hybrid silkworm seed at Silkworm Seed Production Centre (SSPC), Raiganj, Uttar Dinajpur, West Bengal in microclimatic conditions by following standard seed production technique. The hybrid commercial seeds Nistari X M2(W) and its reciprocal, the popular multivitine silkworm hybrids were prepared in West Bengal state for unfavourable Seasons (April to August). The cocoon yield/100 difls, cocoon to pair percentage, pair to difl (disease free laying) percentage and recovery of difls/kg. Seed cocoon were recorded beside agroclimatic, microclimatic parameters i.e. temperature and relative humidity (RH) in learing and grainage period repectively. The results revealed that yield of seed cocoons/100 difls was significantly higher in spring crop followed by the summer and rainy. Similarly, grainage performance in respect of cocoon to pair percentage, pair to dfls percentage and recovery per kg. seed cocoon were significantly higher in Spring season followed by rainy and summer seasons.